Silver Grid Finger Corrosion on Snail Track affected PV Modules – Investigation on Degradation Products and Mechanisms. (November 2016) - Duerr, Ines; Bierbaum, Joerg; Metzger, Jens; Richter, Jannik; Philipp, Daniel
Abstract: The silver grid corrosion phenomenon of c-Si solar cells, often called "snail trails" or "snail tracks", which occurs mainly shortly after installation of PV modules in the field, was first observed approximately one decade ago in the southern part of Europe. It was recognized quickly that these discolorations on the metal grid fingers are always accompanied by cell (micro) cracks. From the herein presented investigations, it can be shown that several different chemical mechanisms and material involvements can lead to the visual phenomenon of silver grid finger discoloration. It must therefore be clarified that the term "snail track" (or "snail trails") only describes a failure class and not a single degradation mechanism. This work focuses on a bottom up approach, which includes the chemical analyses of the affected cell parts extracted from various industrial modules which have been installed in the field. In addition to the analytical investigations after field failure, the modules are exposed to artificial stresses to investigate the development, formation or further reaction of the snail track degradation products. Since the phenomenon is always accompanied by diffusion open areas in the module (cell gaps, cell cracks), the diffusion of reactant partners from the rear side of the module, e.g. atmospheric gases or additives from the back sheet material, has been the most suspected root cause from the beginning of the observation. The role of these reaction partners is therefore highlighted within the results. Four different snail track degradation products have been identified until now: Silver carbonate, silver sulfide, silver phosphate and silver acetate. Silver sulfide snail tracks were only found after damp-heat test (only artificially induced), all other types were found from field failed PV modules and respectively partially from stress tests. The different snail track types, materials and module components considered being involved and the formation mechanisms are presented in this work.